Description of body image perception and its relation to nutrient intake in bodybuilders - Sarli Mohd; Riyadi Hadi; Setiawan Budi; Dzulhijjah Rahmi (BIO Web of Conferences)
Background: The problem of body dissatisfaction affects the perception of body image in bodybuilders. Objective: This study aims to determine the perception of body image and its relationship with nutrient intake in bodybuilders. Methods: A cross-sectional study was conducted involving 70 bodybuilders during the cutting phase of their training. Energy and nutrient intake data were collected through 24-hour Food Recall interviews for 2 days. Muscle mass and fat mass data were obtained by Bioelectrical Impedance Analysis (BIA). Body image perception data using the Bodybuilder Image Grid. Statistical analysis uses Spearman rank analysis. Results: Most bodybuilders were in early adulthood (aged 26-45 years), highly educated, employed in permanent jobs, and had incomes in the high category. The BMI was classified as normal, while the Fat-Free Mass Index (FFMI) in the competitive group was predominantly average, and in the non-competitive group, it was mostly below average. The group of non-competitive bodybuilders felt dissatisfied with their body shape based on fat mass and muscle mass, which was different from the group of competitive bodybuilders who felt satisfied with their body shape based on body fat mass It was found that carbohydrate intake was associated with body image perception, particularly in relation to fat mass (p<0.01). Conclusions: Bodybuilders want a leaner body (low body fat mass percentage) and muscularity (high muscle mass percentage) by adopting a low carbohydrate and fluid diet.